Efficiency research of the criterions for implementation of separated lane for buses using visum - Зубачик, Роман Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
The article presents verification of the proposed criteria for implementation special bus lanes and efficiency of their use in real conditions, namely in the city street spacing. VISUM helps determine the parameters of public transport work, in particular the bus operational speed and delays at stops. Results obtained by using VISUM show that they are close to those obtained in natural studies. The model adequacy to real conditions made it possible to check the feasibility of introducing special bus lanes on street spacing according to the three criteria and find out the operational speed of a bus in cases where special bus lanes are available and unavailable on the street, and assess the impact of introduction of special bus lanes on changes of traffic flows both at the local level (within a street spacing’s) and in the city in general. The obtained results of studies point out to efficiency of the proposed criteria of introduction of special bus lanes on street spacing, their simplicity in use and feasibility.